2015
DOI: 10.18517/ijaseit.5.1.474
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Properties of Restructured Sweetpotato Stick from Three Sweetpotato Cultivars

Abstract: Restructured Sweetpotato Stick (RSS) was developed in attempt to overcome the lack of sweetpotato availability during off season. Moreover, RSS was produced aimed to control of the adequate qualities caused by the variation characteristics of sweetpotato. The making of RSS from 3 sweetpotato varieties was to study physicochemical and sensory attributes of the final product. RSS was produced using three sweetpotato (SP) varieties with different flesh colour namely White, Yellow and Orange. Samples, including ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 17 publications
1
5
4
Order By: Relevance
“…The starch content of the genotypes in their study was in the range of 22.4% to 27.7%. Utomo and Rahman (2015) reported that the white cultivar had the highest starch content (19.30%) which is however higher than the values obtained for the white-fleshed genotypes in this study (Table 1). Utomo (2015) reported starch content to be significantly different (p < 0.05) among three cultivars (white, yellow, and orange).…”
Section: Starch Content Of Sweetpotato Rootscontrasting
confidence: 85%
See 4 more Smart Citations
“…The starch content of the genotypes in their study was in the range of 22.4% to 27.7%. Utomo and Rahman (2015) reported that the white cultivar had the highest starch content (19.30%) which is however higher than the values obtained for the white-fleshed genotypes in this study (Table 1). Utomo (2015) reported starch content to be significantly different (p < 0.05) among three cultivars (white, yellow, and orange).…”
Section: Starch Content Of Sweetpotato Rootscontrasting
confidence: 85%
“…These values fall within those obtained in this study. Utomo and Rahman (2015) reported that the white cultivar had the highest starch content (19.30%) which is however higher than the values obtained for the white-fleshed genotypes in this study (Table 1). The pale yellow-fleshed genotype was rather found to have the highest starch content value in this study.…”
Section: Starch Content Of Sweetpotato Rootscontrasting
confidence: 85%
See 3 more Smart Citations